Heat-treatment process and peening intensity on abrasive wear response of agricultural grade boron steel in dry sand and slurry - SINGH, DUSHYANT; MONDAL, D P (The Indian Journal of Agricultural Sciences, 2012)
The aim of present study is to understand the low stress abrasive wear response of heat-treated and shot peened agricultural grade boron steel under dry and slurry conditions. Heat-treatment (annealing, inter-critical annealing and quenching and tempering) was carried out to alter the mechanical as well microstructural properties of steel. The surface properties were further improved by shot peening carried out at 0.17 A and 0.27 A peening intensities. The wear test methodology adopted in this study is very well simulated with working condition of soil working fast wearing components of agricultural implements like cultivator sweeps, furrow opener of seed drills and plough share etc. The study reveals that the heat-treatment and shot peening together improve the abrasive wear resistance of boron steel significantly in dry condition but heat-treatment does not have any significant effect on abrasive wear resistance in slurry due to the presence of corrosive media, besides shot peening under such circumstances leads to inferior wear resistance. This technique is found promising to improve the quality of soil working agricultural components working in dry condition but not fruitful in slurry condition.